Incidence and risk‐factors of CHOP/R‐CHOP‐related cardiotoxicity in patients with aggressive non‐Hodgkin's lymphoma. (3rd January 2014) - Limat, S.; Daguindau, E.; Cahn, J.‐Y.; Nerich, V.; Brion, A.; Perrin, S.; Woronoff‐Lemsi, M.‐C.; Deconinck, E.
Summary What is known and objective The CHOP regimen with rituximab (R‐CHOP) remains the standard for chemotherapy in patients with aggressive non‐Hodgkin's lymphoma (NHL). The cardiotoxicity of doxorubicin appears to be a key problem in clinical practice. We studied the cardiotoxicity of CHOP/R‐CHOP regimen in a retrospective series. The prognostic factors of congestive heart failure (CHF) were investigated, including the impact of empirical cardioprotection by dexrazoxane. Methods Patients with an aggressive NHL between 1994 and 2005 were included. Cardiac events were defined as either a decline in resting left ventricular ejection fraction (LVEF) <50%, a decline in LVEF of ≥20% from baseline or as clinical evidence of CHF. The risk of cardiotoxicity was explored by the Kaplan–Meier method. Results The study included 180 consecutive patients. During the second period of the survey, cardioprotective therapy by dexrazoxane was administered to 45% of patients. The 5‐year cumulative risks of cardiac events (29% vs. 8%) and clinical CHF (17% vs. 1·5%) varied significantly between the two periods of study (1994–2000 vs. 2001–2005). In multivariate analysis, use of dexrazoxane (HR = 0·1 [0·01–0·75], P = 0·02) and age < 60 years (HR = 0·4 [0·17–0·9], P = 0·03) appeared as protective factors of cardiac events. What is new and conclusion Our study confirmed the weight of cardiac toxic effect of CHOP ± R regimen. Even if the use of dexrazoxane is highly debatable in curative situations, it may be an effective prevention of cardiotoxicity in aggressive NHL patients.